A genome‐wide association study identifies a region strongly associated with symmetrical onychomadesis on chromosome 12 in dogs. (14th September 2016) - Dahlgren, S.; Ziener, M. Lund; Lingaas, F.
Summary: Symmetrical onychomadesis causes periodic loss of claws in otherwise healthy dogs. Genome‐wide association analysis in 225 Gordon Setters identified a single region associated with symmetrical onychomadesis on chromosome 12 (spanning about 3.3 mb). A meta‐analysis including also English Setters indicated that this genomic region predisposes for symmetrical onychomadesis in English Setters as well. The associated region spans most of the major histocompatibility complex and nearly 1 Mb downstream. Like many other autoimmune diseases, associations of symmetrical onychomadesis with DLA class II alleles have been reported. In this study, no associated markers were revealed within any of the DLA‐DRB1, ‐ DQA1 or ‐ DQB1 genes, and the odds for symmetrical onychomadesis in the Gordon Setters were much higher, carrying significant single nucleotide polymorphisms compared to the odds of any of the recorded DLA‐DRB1/DQA1/DQB1 haplotypes. We noticed that some of the associated DLA haplotypes were different between the English Setters and the Gordon Setters. Interestingly, associated SNP chip markers showed a more consistent pattern of allelic variants related to cases or controls regardless of breed. In conclusion, the associated genetic markers identified in this study hold the potential to aid in selection of breeding animals to reduce the frequency of symmetrical onychomadesis in the dog.